THU0402 Do we have good instruments to predict major cardiovascular events in systemic sclerosis patients?. (12th June 2018) - Radu, C.; Groseanu, L.; Gudu, T.; Balanescu, A.; Predeteanu, D.; Bojinca, V.; Opris-Belinski, D.; Borangiu, A.; Saulescu, I.; Daia-Iliescu, S.; Constantinescu, C.; Mazilu, D.; et al.
Abstract : Background: While macrovascular disease and higher cardiovascular (CV) risk are well documented in other systemic rheumatic diseases, the risk for major cardiovascular events for patients with systemic sclerosis (SSc) is yet to be established. Objectives: The aim of the study was to determine the ability of different cardiovascular risk indices to predict major cardiovascular events (MACE) in systemic sclerosis. Methods: The study included 144 patients followed in EUSTAR centre 096, but only patients with a follow-up for more then 10 years were selected for statistical analyses. Cardiovascular risk was estimated using QRiskII, systemic coronary risk evaluation ( SCORE ) and ACC/AHA risk indices. MACE were defined as: myocardial infarctions, strokes, peripheral vascular disease and cardiovascular related death. Data were compared by non-parametric tests. Results: 32 patients, 31 females, 12 diffuse SSc subsets were included. The control group included 30 age and sex matched patients without autoimmune diseases. Mean age of the group was 52 years±SD 9.7, mean disease duration was 8 years±SD 9. The prevalence of traditional risk factors was: 13% smokers, significant family history 38%, obesity 16%, dyslipidemia 32%, older age 13%, hypertension 16%. There were no significant differences from the control group. Major cardiovascular events were: 13% myocardial infarction, 9% peripheral vascular disease, 9% CV related deaths. Concerning CV risk indices of the 32 SSc patients, 4 (13%) were classified as having high CV risk according to QRiskII/SCORE/ ACC risk.. In SSc patients, we could not identify any correlation between the above mentioned risk indices and MACE, including death of cardiovascular causes, except for a slight correlation between the SCORE and cardiovascular related death (p=0.04). Conclusions: In our study, the main prediction indices were not correlated with the 10 year risk for CV events in SSc patients suggesting that we need better risk prediction tools. Both traditional risk factors and endothelial dysfunction have been proposed to participate at the onset and progression of vascular disease in SSc. Special attention should be paid to correct the traditional risk factors in combination with specific treatment for SSc. References: [1] Psarras A, Soulaidopoulos S, Garyfallos A, Kitas G, Dimitroulas T A critical view on cardiovascular risk in systemic sclerosis. Rheumatol Int2017;37(1):85–95. [2] Groseanu L, Bojinca V, Gudu T, Saulescu I, Predeteanu D, Balanescu A, et al. Low vitamin D status in systemic sclerosis and the impact on disease phenotype Eur J Rheumatol2016;3(2):50–55. Disclosure of Interest: None declared